DIURNAL VARIATIONS IN PLANT WATER RELATIONS OF WHEAT CULTIVARS AS INFLUENCED BY SOIL MOISTURE REGIMES UNDER SHALLOW WATER TABLE CONDITIONS - TOMAR, R.K.; Tripathi, R.P.; Garg, R.N.; Gupta, V.K.; CHAKRABORTY, D.; SAHOO, R.N.; KALRA, NAVEEN (Annals of Agricultural Research, 2014)
Field experiments were conducted in silty clay loam (Typic Hapludoll) at GBPUA&T, Pantnagar (Uttaranchal). to study the effect of soil moisture regimes on diurnal variations in plant water relationships, growth and productivity for selecting wheat cultivars and also to find out their suitability under shallow water table conditions in Tarai regions. Treatments consisted of soil moisture regimes (five) in main-plot and wheat cultivars (eight) in sub-plot. Marked differences in diurnal variations in plant water relations viz., xylem water potential, transpiration rate, leaf diffusive resistance, and canopy minus air temperature difference in all the cultivars started appearing on 52 days after sowing (DAS) and the maximum differences were observed near flowering stage i.e., 93 DAS. Maximum differences in these parameters were found during 1330-1400 hrs. Soil moisture regimes have significantly influenced the growth parameters (plant height, number of tillers and 1000-grain weight) and grain yield of the cultivars and the interactions were also significant. Based on growth, yield and plant water relations parameters, cultivars C 306, UP 2113 & WL 410, UP 115 & RR 21 and UP 368, HD 2281 & HD 2285 and were suitable under rain fed, limited water (irrigation at CRI) and well-watered (irrigations at CRI and flowering stages) conditions, respectively.